Question Number 110173 by ajfour last updated on 27/Aug/20

Answered by Olaf last updated on 27/Aug/20
![t_n = Σ_(r=1) ^n t_r −Σ_(r=1) ^(n−1) t_r t_n = ((n(n+1)(n+2)(n+3))/8)−(((n−1)n(n+1)(n+2))/8) t_n = ((n(n+1)(n+2)[n+3−n+1])/8) t_n = ((n(n+1)(n+2))/2) t_r = ((r(r+1)(r+2))/2) (1/t_r ) = (2/(r(r+1)(r+2))) = (1/r)−(2/(r+1))+(1/(r+2)) Σ_(r=1) ^n (1/t_r ) = Σ_(r=1) ^n (1/r)−2Σ_(r=1) ^n (1/(r+1))+Σ_(r=1) ^n (1/(r+2)) Σ_(r=1) ^n (1/t_r ) = Σ_(r=1) ^n (1/r)−2Σ_(r=2) ^(n+1) (1/r)+Σ_(r=3) ^(n+2) (1/r) Σ_(r=1) ^n (1/t_r ) = Σ_(r=1) ^n (1/r)−2(Σ_(r=1) ^n (1/r)−1+(1/(n+1))) +(Σ_(r=1) ^n (1/r)−1−(1/2)+(1/(n+1))+(1/(n+2))) Σ_(r=1) ^n (1/t_r ) = 2−(2/(n+1))−(3/2)+(1/(n+1))+(1/(n+2)) Σ_(r=1) ^n (1/t_r ) = (1/2)−(1/(n+1))+(1/(n+2)) Σ_(r=1) ^n (1/t_r ) = (1/2)−(1/((n+1)(n+2))) lim_(n→∞) Σ_(r=1) ^n (1/t_r ) = (1/2)](https://www.tinkutara.com/question/Q110213.png)
Commented by ajfour last updated on 27/Aug/20

Answered by Dwaipayan Shikari last updated on 27/Aug/20

Commented by ajfour last updated on 27/Aug/20
